(untitled) (Andamios, Revista de Investigación Social, 2010)
The author provides analysis elements to understand the intrinsic contradictions of Nation-State model with regard to the real ethnocultural diversity and the modern ideal of ethno-cultural homogeneity in Mexico. This constitutes a first step to base the hypothesis of the work: the necessity to journey from a multicultural reality to an intercultural eutopian scene, for which it´s necessary, as well, an integral reform of the State. Thus, the author display a brief analysis of the constitutional reform in the matter of rights of the indigenous peoples, and indicates the relevance to reopen the legislative process to correct the deficiencies of the constitutional reform, like a minimum legal floor to arrive at this intercultural scene.